Put a little more thought into this.

Algebra Level 3

f ( x ) = x 4 8 x 3 + 18 x 2 8 x + 2 \large f(x)= x^4 - 8x^3 + 18x^2 - 8x +2

Evaluate the value of f ( 2 + 3 ) f(2+\sqrt 3) for the function above.


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Oct 16, 2016

f ( x ) = x 4 8 x 3 + 18 x 2 8 x + 2 = x 4 8 x 3 + 24 x 2 32 x + 16 6 x 2 + 24 x 14 = ( x 2 ) 4 6 ( x 2 4 x + 4 ) + 10 = ( x 2 ) 4 6 ( x 2 ) 2 + 10 f ( 2 + 3 ) = ( 3 ) 4 6 ( 3 ) 2 + 10 = 9 18 + 10 = 1 \begin{aligned} f(x) & = x^4-8x^3+18x^2-8x+2 \\ & = x^4-8x^3+24x^2-32x+16-6x^2+24x-14 \\ & = (x-2)^4 - 6(x^2-4x+4) + 10 \\ & = (x-2)^4 - 6(x-2)^2 + 10 \\ \implies f(2+\sqrt 3) & = (\sqrt 3)^4-6(\sqrt 3)^2+10 \\ & = 9 - 18 + 10 \\ & = \boxed{1} \end{aligned}

+1. The most elegant method. :)

Tapas Mazumdar - 4 years, 8 months ago
Zee Ell
Oct 15, 2016

f ( x ) = x 4 8 x 3 + 18 x 2 8 x + 2 = ( x 4 8 x 3 + 17 x 2 ) + ( x 2 8 x + 17 ) 15 = f(x) = x^4 - 8x^3 + 18 x^2 - 8x + 2 = (x^4 - 8x^3 + 17 x^2) + (x^2 - 8x + 17) - 15 =

= ( x 2 + 1 ) ( x 2 8 x + 17 ) 15 = (x^2 + 1) (x^2 - 8x+ 17) - 15

Since

( 2 + 3 ) 2 = 7 + 4 3 (2+ \sqrt {3} )^2 = 7 + 4 \sqrt {3}

therefore:

f ( 2 + 3 ) = ( 8 + 4 3 ) ( 7 + 4 3 16 8 3 + 17 ) 15 = f(2+ \sqrt {3} ) = (8 + 4 \sqrt {3} )(7 + 4 \sqrt {3} - 16 - 8 \sqrt {3} + 17) - 15 =

= ( 8 + 4 3 ) ( 8 4 3 ) 15 = 64 48 15 = 1 = (8 + 4 \sqrt {3} )(8 - 4 \sqrt {3}) - 15 = 64 - 48 - 15 = \boxed {1}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...